Beban Kerja, Konflik Peranan, Tekanan Kerja dan Prestasi Kerja di Kalangan Pegawai Perubatan - Jezlily, Jamaluddin (2011)
This study investigate job performance of medical officers who are do the clinical work as well as the management and admnistration tasks. Workload and role conflict were considered as the independent variables, job stress as the mediating variable while job performance as the dependent variable. A survey of 126 medical officers working in hospitals Klang Valley was conducted. The findings show that job stress has no effect as a mediator on workload, role conflict and job performance. The implications of the findings to practice and future research, and the limitations of the study are discussed.